O valor do Netflix para o consumidor brasileiro - Amaral, Marcela Rodrigues do (2016)
The increase of internet penetration and mobility enabled the appearance of new players that offer online media subscription. Today Netflix is the largest of these players, with 87 subscribers around the world. The on demand model is already a reality for some Brazilian consumers. The option to customize the use of such platform changes the experience of the consumer, as it is possible to shape the users viewing experience to reflect their personal preferences and time availability. The objective of this dissertation is to understand the value that Netflix offers to the Brazilian consumer. To achieve this objective, other´s authors hypothesis were verified and new hypothesis were drawn. The conclusions were based on the answers of 225 responses to an online questionnaire, as well as some interviews. Among the main conclusions, we highlight three points. The first is that the greatest value for the consumers consisted in having the option to use the platform wherever and whenever they wished. The second point regards the kind of content offered: the international content was the highlight for being the most watched, while consumers indicated that the sports and news content was in short supply. The third point was a suggestion for a possible improvement to the product. The answers indicate that consumers would also like to have the ability to use the platform while offline. This point was indicated mainly because of the poor internet service in Brazil, which could momentarily block the access to online streaming services.